Scientific and practical substantiation of directions of mutual cooperation of higher educational institutions with employers of pharmaceutical sector of health care industry - Barkovska, Oksana; Ogar’, Svetlana; Rohulia, Olha (ScienceRise: Pharmaceutical Science, 2018)
The aim is to study, summarize and develop the directions of mutual cooperation between higher education institutions with employers of the pharmaceutical sector of the healthcare industry, which will allow making the preparation of competitive competent specialists in accordance with the requirements of the labor market. Methods: to achieve the aim, methods of scientific analysis were used, in particular generalization, comparison, system and logical methods. Graphic analysis is used to visualize the generalized results of the expert survey. Results: scientific and practical approaches to determining directions of mutual cooperation between higher education institutions and employers of the pharmaceutical sector of the healthcare industry are substantiated. Modern directions of cooperation between higher education institutions and employers are presented, which contribute to the improvement of the organizational and methodological foundations of interaction, the optimization of the content of education and the educational process, the improvement of the quality of practical training and employment of graduates, the development of research and innovation infrastructure. The forms of cooperation of the National University of Pharmacy (NUPh) with pharmacy institutions and pharmaceutical enterprises are systematized, the introduction of which will improve the quality of practical training of pharmacists. Conclusions: based on the results of the expert survey of pharmacy specialists, it is determined that the most significant motivations for the cooperation of the National University of Pharmacy with the employers of the pharmaceutical sector of the healthcare sector are the training of specialists in accordance with the labor market needs and access to skilled labor resources, and effective forms of cooperation - mentoring and training. Based on the results of the research on the specifics and forms of cooperation, the authors carried out their systematization and defined the areas of mutual cooperation between higher education institutions and employers, using the example of the NUPh, the implementation of which contributes to improving the quality of practical training for future pharmacists and the formation of competitive graduates in accordance with labor market requirements